1982
DOI: 10.2307/1938874
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fine Roots in the Organic Matter and Nitrogen Budgets of Two Forested Ecosystems

Abstract: Standing crop, rates of production, mortality, decomposition, and nitrogen dynamics of two size classes of fine roots (0—05 mm and 0.5—3.0 mm diameter) were estimated for 1 yr in a 53—yr—old red pine (Pinus resinosa Ait.) plantation and in an adjacent 80—yr—old mixed hardwood stand in north—central Massachusetts. Dry matter of live fine roots was higher in the hardwoods (mean = 6.1 Mg/ha; annual range 3.6—8.6 Mg/ha) than in the plantation (mean = 5.1 Mg/ha; annual range 2.5—7.8 Mg/ha.) Dead root mass was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
286
7
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(308 citation statements)
references
References 37 publications
11
286
7
4
Order By: Relevance
“…This seasonal pattern seems to correspond roughly to leaf duration. In temperate forests, the most significant period of root growth corresponds to canopy development in the spring and the most significant period of root mortality corresponds to canopy senescence in the fall (McClaugherty et al, 1982 ;Kurtz & Kimmins, 1987 ;Hendrick & Pregitzer, 1992, 1993a, 1996. Root-shoot phenological observations of temperate trees presented by Lyr & Hoffmann (1967) suggest that most of the flush of fine-root growth in the spring might occur after canopy development.…”
Section:  mentioning
confidence: 99%
“…This seasonal pattern seems to correspond roughly to leaf duration. In temperate forests, the most significant period of root growth corresponds to canopy development in the spring and the most significant period of root mortality corresponds to canopy senescence in the fall (McClaugherty et al, 1982 ;Kurtz & Kimmins, 1987 ;Hendrick & Pregitzer, 1992, 1993a, 1996. Root-shoot phenological observations of temperate trees presented by Lyr & Hoffmann (1967) suggest that most of the flush of fine-root growth in the spring might occur after canopy development.…”
Section:  mentioning
confidence: 99%
“…Studies have indicated that litter input belowground could account for 6.2-88.7% (average 50%) those aboveground and constitute 14-86.6% (most above 40%) of total soil organic input (e.g., [27,44]). In the present study, C inputs belowground in the NF almost equaled those aboveground, and amounted to about half of aboveground C input respectively in the plantations.…”
Section: Litterfall C Inputsmentioning
confidence: 99%
“…However, an estimation of fine root production could be calculated at the stand level by using an annual turnover ratio of 0.6 and using the method devised by MacClaugherty et al [26] to estimate annual fine root production. The turnover ratio, defined here as the ratio between the production of fine roots during the growing season and the biomass of living fine roots at the end of the growing season, was derived from data obtained by Farque on the same site (unpublished data).…”
Section: Biomass Increment Relationsmentioning
confidence: 99%